Improvement instead of stability in embryo quality between day 3-5: A possible extra predictor for blastocyst selection. (October 2020) - Blank, C.; DeCroo, I.; Weyers, B.; van Avermaet, L.; Tilleman, K.; van Rumste, M.; de Sutter, P.; Mischi, M.; Schoot, B.C.
Highlights: Day-5 embryo scoring is more predictive for ongoing pregancy outcome than the same scoring on day 3. Selection of blastocyst-stage embryos should initially be based on the established day 5 variables. Dynamic evaluation of the embryo quality between day 3–5 should be considered as a second parameter. Abstract: Objective: The aim of this study was to evaluate the predictive value of the dynamic morphological development process between cleavage-stage and blastocyst-stage embryos. Study design: A retrospective study was executed between 2015 and 2017 at Ghent University Hospital. A total of 996 first fresh IVF/ICSI cycles resulting in a single embryo transfer on day 5 were included. Embryos were scored on day 3 and day 5 as excellent, good, moderate or poor based on Alpha/ESHRE guidelines and Gardner and Schoolcraft scoring-system. If embryos changed category between day 3 and 5, the number of steps (between excellent; good; moderate; poor) in positive and negative direction was expressed. Results: On day 5, the ongoing pregnancy rate (OPR) of excellent embryos was 37.4 %. Univariate analyses showed that on day 5, both a higher cell stage, better inner cell mass and better trophectoderm were significantly associated with an ongoing pregnancy. In case of deterioration in quality of individual embryos between day 3 and day 5, the OPR was significantly lower. Conversely, improvement of embryo quality between day 3 and day 5 showed higher ongoing pregnancy rates (overall OPR of good day-3 embryos improving to excellent day-5 embryos: 30 %; moderate day 3 to excellent day 5: 50 %; poor day 3 to excellent day 5: 42 %; poor day 3 to good day 5: 20 %; poor day 3 to moderate day 5: 16 %). When embryos improved from poor on day 3 to excellent day 5 the OPR was significantly higher in comparison with embryos that did not change in quality scoring during development (steady embryos) (OR: 1.785, p < 0.05). Conclusion: Our results suggest that it is more likely to achieve an ongoing pregnancy when transferring an embryo that has improved in quality between days 3 and 5 as opposed to one that has remained stable.